2002
DOI: 10.1002/1522-2683(200203)23:6<903::aid-elps903>3.0.co;2-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence polarization detection for affinity capillary electrophoresis

Abstract: Affinity capillary electrophoresis (ACE) with laser-induced fluorescence polarization (LIFP) detection is described, with examples of affinity interaction studies. Because fluorescence polarization is sensitive to changes in the rotational motion arising from molecular association or dissociation, ACE-LIFP is capable of providing information on the formation of affinity complexes prior to or during CE separation. Unbound, small fluorescent probes generally have little fluorescence polarization because of rapid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 24 publications
1
33
0
Order By: Relevance
“…In fact, CE/LIFP analysis not only provides the information on electrophoretic mobility (derived from migration), but also offers the information on the diffusional rotation of the analytes (fluorescence polarization). It has been demonstrated that the FP values can be used to differentiate between the unbound aptamers and the protein bound aptamer complexes even when they are not well separated [35,36]. Therefore, here we used the CE/LIFP approach to identify the thrombin-aptamer complex in CE separation of complex matrix.…”
Section: Complex Formation and Ce Separationmentioning
confidence: 99%
“…In fact, CE/LIFP analysis not only provides the information on electrophoretic mobility (derived from migration), but also offers the information on the diffusional rotation of the analytes (fluorescence polarization). It has been demonstrated that the FP values can be used to differentiate between the unbound aptamers and the protein bound aptamer complexes even when they are not well separated [35,36]. Therefore, here we used the CE/LIFP approach to identify the thrombin-aptamer complex in CE separation of complex matrix.…”
Section: Complex Formation and Ce Separationmentioning
confidence: 99%
“…Since the discovery of aptamers in 1990s, aptamer-based assays for small molecules have drawn increasing attentions in environmental sensing, food safety, and clinical analysis due to the unique features of aptamers, such as easy generation, facile labeling, good thermal stability, small size, and target-binding induced structure change (Citartan et al, 2012;Feng et al, 2014;Juskowiak, 2011;Kim and Gu 2014;Li et al, 2015;Liu et al, 2009;McKeague and Derosa, 2012). Taking advantage of fluorescence anisotropy (FA) or fluorescence polarization (FP) in sensitivity, reproducibility, and simplicity (Lea and Simeonov, 2011;Gradinaru et al, 2010;Le et al, 2002;Smith and Eremin, 2008), the aptamer-based FA/FP sensors are attractive Liu et al, 2009;Ruta et al, 2009;Zhang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…1). A similar approach has been used to study oder interactions, such as antibodydigoxin, antibody-gentamicin, and antibody-vancomycin [77][78][79][80][81]. When in a CE system at a low concentration of protein as additive a steady state is reached, the additive entering the analyte plug is unaffected by the mobility of the additive.…”
Section: Protein-small Molecule Interactionmentioning
confidence: 99%